Volatile compounds produced by microorganisms isolated from cork - Caldentey, Paloma; Fumi, Maria Daria; Mazzoleni, Valeria; Careri, Maria (Flavour and Fragrance Journal, 1998)
Microorganisms present on cork (i.e. the reproduction bark of Quercus suber L.) can produce odorous compounds aecting the quality of cork stoppers. This work aims to contribute to the study of the correlation between microbial growth and formation of volatile compounds in the cork. Dierent strains of microorganisms were cultivated on both malt extract and cork, and the odour of the culture was described by a panel. The volatile compounds were isolated directly from the culture media by a dynamic headspace technique followed by adsorption on to Tenax traps. The volatiles were identi®ed by GC±MS: 63 substances were identi®ed in malt extract cultures, mainly consisting of carbonyl compounds (16), alcohols (16), and sesquiterpenes (13). Cultures on cork produced only 12 volatile compounds, more than half being sesquiterpenes. Sensory evaluation con®rmed that cork is an unfavourable culture medium if compared with malt extract.
Keywords: Cork; microbial growth; Quercus Suber L; volatile components

GC−MS Study of Volatiles of Normal and Microbiologically Attacked Cork from Quercus suber L. - Rocha, Sílvia; Delgadillo, Ivonne; Ferrer Correia, A. J. (Journal of Agricultural and Food Chemistry, 1996)
The volatile compounds of cork were studied by gas chromatography and combined gas chromatography?high-resolution mass spectrometry using simultaneous distillation?extraction to prepare the samples. To assess the origin of the volatiles, three different types of samples were analyzed:? ?normal?, attacked by Armillaria mellea, and infested by molds. The study of the volatiles of these different types of corks allowed the identification of the chemical modifications which may occur in cork polymers. The cork attacked by A. mellea showed higher amounts of phenols, vanillin, benzaldehyde, benzyl alcohol, and chlorinated compounds than normal cork; this may indicate lignin degradation. The cork infested by molds contained higher levels of 3-methyl-1-butanol, 1-octen-3-ol, 1-octanol, 2-methylisoborneol, chlorinated compounds, and methyl ketones. These components resulting from microbial metabolism were also present in cork attacked by A. mellea. The use of cork attacked by A. mellea is not recommended in the manufacture of cork stoppers, since these types of cork have volatile compounds likely to cause off-flavors in wine. For the same reason it is important to reduce the likelihood of mold development during the standing period. Keywords: ?Normal? cork; Armillaria mellea; molds; volatile components; musty and moldy odors
doi: 10.1021/jf9500400doi: 10.1021/jf9500400The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Armillaria mellea; molds; musty and moldy odors; volatile components; “Normal” cork

GC−MS Study of Volatiles of Normal and Microbiologically Attacked Cork from Quercus suber L. - Rocha, Sílvia; Delgadillo, Ivonne; Ferrer Correia, A J (Journal of Agricultural and Food Chemistry, 1996)
The volatile compounds of cork were studied by gas chromatography and combined gas chromatography?high-resolution mass spectrometry using simultaneous distillation?extraction to prepare the samples. To assess the origin of the volatiles, three different types of samples were analyzed:? ?normal?, attacked by Armillaria mellea, and infested by molds. The study of the volatiles of these different types of corks allowed the identification of the chemical modifications which may occur in cork polymers. The cork attacked by A. mellea showed higher amounts of phenols, vanillin, benzaldehyde, benzyl alcohol, and chlorinated compounds than normal cork; this may indicate lignin degradation. The cork infested by molds contained higher levels of 3-methyl-1-butanol, 1-octen-3-ol, 1-octanol, 2-methylisoborneol, chlorinated compounds, and methyl ketones. These components resulting from microbial metabolism were also present in cork attacked by A. mellea. The use of cork attacked by A. mellea is not recommended in the manufacture of cork stoppers, since these types of cork have volatile compounds likely to cause off-flavors in wine. For the same reason it is important to reduce the likelihood of mold development during the standing period. Keywords: ?Normal? cork; Armillaria mellea; molds; volatile components; musty and moldy odors
doi: 10.1021/jf9500400
Keywords: Armillaria mellea; molds; musty and moldy odors; volatile components; “Normal” cork